Natural Disasters Topic in Bahasa Learning Using Project-Based Learning (PJBL) - Armani Armani; Yanti Sudiarti; Widiantoro Dwi (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2023)
The aim of this study is to improve knowledge and understanding of Bahasa in natural disasters topic. The PJBL model was implemented with a quantitative descriptive research approachThe participants were 29 second-grade students at SDN 36 Pontianak. In Cycle 1, 21 students passed with a percentage of 72%, and those who have not passed amounted to 8 students with a percentage of 27%. In cycle II, with improved implementation with an accurate and targeted level using the PjBL Model, 29 students passed (100%). The existence of the PjBL model and understanding of natural disasters can be accepted because the students are given a wide opportunity to conduct smaller and more effective group discussions.